Pengembangan Produk Sambal Bawang dengan Penambahan Tepung Tulang Ikan Lele - Trisnawati, Chatarina Yayuk; Kaharso, Victor Christian; Virly (Universitas Ahmad Dahlan, 2024)
Catfish bones contain high levels of calcium and have the potential to serve as an alternative calcium source. To maximize its benefit, catfish bone meal can be added to onion chili sauce, enhancing the end product’s calcium content. The concentration of added catfish bone meal must be observed to produce onion chili sauce with good characteristics. One common stage in chili sauce processing is frying with oil, which can potentially lead to oxidation in oil and affect the quality of the onion chili sauce. This research aimed to study the effect of concentration of catfish bone meal on the free fatty acid content, peroxide value, and calcium content in onion chili sauce. A randomized block design was employed with the concentration of catfish bone meal as the treatment factor at three levels: 15%, 20%, and 25% of the weight of cayenne pepper. The result showed that the concentration of catfish bone meal significantly influenced the free fatty acid levels of onion chili sauce stored for 28 days, the peroxide value in onion chili sauce stored for one day, and the calcium content of onion chili sauce. There was a notable increase in peroxide value and free fatty acid content over the 28 days storage period in the refrigerator.